Assessment of Hydration Mechanisms, Rheological Behavior, and Sorptivity of Portland Cement Pastes Using Low-Cost Arduino Platform-Based Sensors - Kalsoom Akash; Muhammad Ali Sikandar; Bakht Zamin; Abid Haider; Mahmood Ahmad; Mohanad Muayad Sabri Sabri (Advances in Materials Science and Engineering)
This study assesses hydration, rheology, and sorptivity of cementitious pastes using relatively low-cost Arduino-based platforms with integrated sensors. The prime objective is to develop a correlation between conventional apparatus-based and Arduino-integrated sensor-based assessment. A total of six samples of cementitious paste were prepared at a room temperature of 26°C, with a w/b ratio of 0.3, containing cement, fly ash, and silica fume. First, the conventional apparatus was employed to assess hydration, rheology, and sorptivity of cementitious mixes. Afterward, a platform arranged for data acquisition, comprising Arduino Mega 2560, a temperature sensor, a soil moisture sensor, and a voltage supply, was used to assess the same properties. The recorded temperature and moisture content data were transmitted using the Android application and the Wi-Fi modem router. A 5-minute moisture analysis test was conducted to monitor the rheological behavior of cementitious mixes. The heat of the hydration mechanism was evaluated for 32 hours using a temperature sensor, enabling continuous and real-time monitoring. Moreover, a sorptivity test on cube samples was performed using shielded self-based apparatus in an adiabatic condition, resulting in relatively long-term monitoring. The microscopic details are analyzed by using a scanning electron microscope (SEM) in conjunction with EDX analysis. Thus, the potential application of the inexpensive sensor-based method is verified.